Chemical composition, cytotoxicity and antimicrobial activity of selected plant-derived essential oils against fish pathogens - Assane, Inácio M. [UNESP]; Valladão, Gustavo M. R.; Pilarski, Fabiana [UNESP] (Hindawi, 2021)
The use of essential oils (EOs) is a promising strategy for reducing antibiotic use in aquaculture. In this study, we investigated the chemical composition, in vitro cytotoxicity and antimicrobial activity of 16 commercial plant-derived EOs against Aeromonas hydrophila, A. jandaei and Citrobacter freundii isolated from diseased freshwater fish (Oreochromis niloticus and Pterophyllum scalare). Efficacy of treatment with EOs and four antibiotics used in aquaculture: enrofloxacin, florfenicol, oxytetracycline and thiamphenicol, were compared. The chemical compositions of EOs were determined via high-resolution gas chromatography, and the in vitro cytotoxicity and antimicrobial activity were assessed using a haemolysis assay and the microdilution method respectively. Ninety-four components of EOs were identified. The principal components of most EOs were oxygenated monoterpene hydrocarbons. Most EOs possessed non-cytotoxic effects against fish erythrocytes at concentrations with strong (MIC ≤ 500 µg/ml) and moderate (600 µg/ml ≤ MIC ≤1,500 µg/ml) antimicrobial activity. A. sativum, C. verum, O. basilicum, S. aromaticum and T. vulgaris EOs were the most active against microbial strains assessed. The present study highlights the potential of using EO to control bacterial disease in cultured fish.
Keywords: antimicrobials; drug synergism; fish disease; haemotoxicity; phytochemicals; solvents